Large Print Moral Stories (Paper Back) (Noida : Om books international, 2022)
A delightful book of moral stories, old and new, where each story teaches a lesson to cherish for life. The fascinating illustrations bring these stories to life and make story-time the best time of the day!
The Jackal learns a Lesson, The Glass of Milk, The Box of Biscuits, Anger, After Three days.
Large Print Story Book Moral Stories Learnings For Life.
Keywords: Children - Moral Stories Learning For Life